2003
DOI: 10.1117/12.503186
|View full text |Cite
|
Sign up to set email alerts
|

<title>Exhaustive geometrical search and the false positive watermark detection probability</title>

Abstract: One way of recovering watermarks in geometrically distorted images is by performing a geometrical search. In addition to the computational cost required for this method, this paper considers the more important problem of false positives. The maximal number of detections that can be performed in a geometrical search is bounded by the maximum false positive detection probability required by the watermark application. We show that image and key dependency in the watermark detector leads to different false positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…In the interest of reducing the computational complexity of geometrical synchronization, we adopt K = 2 steerable basis filters, i.e., G 0 (θ) = cos (θ) and G 1 (θ) = cos(θ − π/2) according to Eq. (6). From the sufficient and necessary condition of shiftability [29], the steerable interpolation function b k (ϕ) satisfies the following equation:…”
Section: Derivation Of Interpolation Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interest of reducing the computational complexity of geometrical synchronization, we adopt K = 2 steerable basis filters, i.e., G 0 (θ) = cos (θ) and G 1 (θ) = cos(θ − π/2) according to Eq. (6). From the sufficient and necessary condition of shiftability [29], the steerable interpolation function b k (ϕ) satisfies the following equation:…”
Section: Derivation Of Interpolation Functionmentioning
confidence: 99%
“…The exhaustive search method [5][6][7] iteratively corrects each geometrical distortion in the search space and then evaluates the watermark extracted from the geometrically corrected carrier accordingly. This method generally leads to high computational complexity and a large probability of false positives.…”
Section: Introductionmentioning
confidence: 99%
“…Naive search is not practical for many applications because the cardinality of the set of all coordinate transformations (or subsets such as the set of affine transformations or the set of shifts) is an obstacle for computationally efficient search. It has also been shown that the exhaustive search is prone to false positives, which makes this approach questionable even if computational cost is not a constraint [16].…”
Section: Introductionmentioning
confidence: 99%
“…This grid reference information is usually either the original non-watermarked image -leading to non-blind approaches (5) -, or embedded structure or marker information -leading to blind inversion approaches (6,7,8) . A different blind approach is to perform a geometrical search for the watermark, however this has important drawbacks concerning false positive detection probability, as we explained in (9) .…”
Section: Introductionmentioning
confidence: 99%